Evaluation of Verteporfin as a Photosensitizer With Anticancer Activity Via System Biology Tools: Evaluation of verteporfin as a photosensitizer with anticancer activity - Ahmadzadeh, Alireza; Arjmand, Babak; Razzaghi, Zahra; Bandarian, Fatemeh; Rezaei, Mitra (Journal of Lasers in Medical Sciences, 2025)
Introduction: Verteporfin as a photosensitizer in photodynamic therapy (PDT) is used to inhibit deviant choroidal vascularization. This agent also has an anticancer property. The effective treatment of various tumors such as melanoma by using verteporfin is confirmed. In the present study, the ability of verteporfin in growth inhibition of MKN45 is investigated via protein-protein interaction (PPI) analysis to explore its beneficial role in PDT. Methods: The gene expression profiles of the treated MKN45 cell with verteporfin are mined from the Gene Expression Omnibus (GEO) database and evaluated via PPI network analysis to find the central genes. The central genes are searched in the GeneCards database to find the more related genes to gastric cancer. The expression amounts of the top central genes related to stomach adenocarcinoma are extracted from the University of Alabama at Birmingham Cancer data analysis Portal (UALCAN). Results: Among 2356 significant differentially expressed genes (DEGs), 58 hub-bottlenecks were determined via PPI network analysis. ERBB2, EGFR, CREBBP, CTSD, PSEN1, HRAS, PIK3R1, NRAS, NFKBIA, FOS, CTSB, CALR, NFE2L2, RHOA, CDKN1A, ITGB1, APP, CD44, HSPA5, and HMGCR were pointed out as the crucial genes. The expression amounts of ERBB2, EGFR, CREBBP, CTSD, and PSEN1 genes which were highlighted as critical genes via the directed PPI network were explored for stomach adenocarcinoma. Conclusion: In conclusion, the anticancer property of verteporfin was highlighted. This finding can improve the efficacy of related PDT.